Investigation on different compositions of clay and water to the permeability of the silica sand used in greensand casting mould - A. Azhar; M. Redzuan; H. H. Hazril (Penerbit Universiti Kebangsaan Malaysia, 2022)
Greensand casting is a casting process that uses mixture of silica sand with addition of control additions which are bentonite clay and the presence of water. Control additions influence the mechanical properties of greensand casting mould, for this study focuses on the permeability. Bentonite clay acts as a binder and activated by water to develop strength and plasticity thus the greensand casting mould can be formed. Permeability is ability of gas to pass through the moulding mixture aggregates in order to reduce the defects due to trapped gasses in mould cavity such as blow holes or pin holes. The objective of this study is to investigate the effect of control addition (water and clay) on the permeability number of silica sand sample (tailing sand) from former tin mine site in Tronoh, Perak. Experiments are conducted according to American Foundrymen Society (AFS) standard of procedures. Sand sample is sieved using mechanical sieve shaker to size of 425 µm. Cylindrical test pieces dimensioning of Ø50 mm×50 mm in height from various mixtures of sand-clay–water ratios are compacted by applying three ramming blows of 6666 grams using Ridsdale-Dietert metric standard rammer. The test pieces are tested for permeability with Ridsdale-Dietert permeability meter. The results show that clay and water have affected the permeability of silica sand sample and when more water and clay added, into the moulding mixture, the permeability is found decreased. The appropriate allowable water and clay content are crucial for permeability number of greensand casting mould.